Risk Factors for Infection After Minor Dermatologic Procedures: A Case–Control Study. Issue 12 (18th December 2021) - Matos, Sophia; Sturm, Brea; Buhnerkempe, Michael; Larson, Rebecca; Wilson, Morgan
Abstract : BACKGROUND: There are limited published data regarding the incidence and risk factors for infection after minor dermatologic procedures, such as skin biopsy, shave, and curettage. Prior studies of infection risk after dermatologic procedures have often not specified the method of preparation of local anesthetic. OBJECTIVE: To assess the incidence and risk factors for infection after minor procedures performed in a general dermatology clinic using buffered lidocaine prepared in office. MATERIALS AND METHODS: In this retrospective case–control study, the medical record was searched for cases of infection after skin biopsies, shaves, conventional excisions, and destructions performed in a general dermatology clinic over a 4-year period. Patient and procedure characteristics were compared with uninfected controls. RESULTS: Of 9, 031 procedures performed during the study period, there were 34 infections (0.4%). The odds of infection for procedures on the arm and leg were 5.29 and 9.28 times higher, respectively, than those on the head/neck. There was no significant effect of age, sex, smoking, immunosuppression, diabetes, or anticoagulation. CONCLUSION: The incidence of infection is low after minor dermatologic procedures performed with local anesthesia using buffered lidocaine prepared in office. There is a higher risk of infection on the arm and leg compared with the head and neck.